TRANSFORMASI PERPUSTAKAAN DESA KARANG SIDEMEN SEBAGAI LUMBUNG LITERASI BERBASIS INKLUSI SOSIAL PERPUSNAS - Ahmad Azzanul Toyyib; Baiq Safinatun Naja; Fadhela Hania Sukmana; Nadira Ain Aziziah; Nurwulan Silviana; Peri Rusdi Julianto; Qurratul Aenun; Rozy Mursyidan Anfasah; Rubianti Rubianti; Urvi Azizah; Warda Hilya Firdauzi; M. Tahir (Jurusan Ilmu Pendidikan, FKIP, Universitas Mataram, 2025)
Low literacy rates among the public, particularly in rural areas, pose a challenge to realizing Indonesia's Golden Generation 2045. This study analyzes the transformation process of the Karang Sidemen Village Library into a “Literacy Barn” through a thematic literacy community service program (KKN) by Mataram University students in collaboration with the National Library. This service project employs a participatory approach involving the community and village officials, divided into three stages: preparation, implementation, and evaluation. The activities were conducted over 45 days, comprising 14 programs focused on improving reading and writing skills and fostering children's interest in reading through play-based learning approaches, such as creating characters from playdough and rewriting stories. The results of the activity showed a significant increase in children's interest and active participation in Selojan Village, marked by the emergence of initiatives to voluntarily reread stories. However, the evaluation confirmed that the program's reach was still very limited in the village where the library is located due to distance factors and low interest from other villages. It was concluded that the program successfully initiated an increase in literacy, but more proactive outreach strategies are needed, such as intensifying the “Literacy Visits to Schools” program to ensure equitable impact across all villages.